Safety and immunogenicity of Ad5-nCoV administered intradermally by needle-free injector in rats - Chen, Li; Zhang, Xiaoyin; Jin, Lairun; Hou, Lihua; Zhu, Fengcai; Li, Jingxin (Frontiers in Medicine, 2025)
ObjectivesTo evaluate the safety and immunogenicity of adenovirus type 5 vectored COVID-19 vaccine (Ad5-nCoV), by intradermal immunization with a needle-free injector in rats.MethodsThis study was divided into two parts. In study A, 105 rats were randomly assigned to seven groups, to receive the low-dose, medium-dose, or high-dose vaccine by needle-free intradermal injections (NFI), or needle-based intramuscular injections (NI), or needle-free intradermal injections with saline solution as a control group. Blood samples were collected on day 0 before vaccination, and day 7, day 14, day 21 and day 28 after vaccination. Binding antibody, pseudovirus neutralizing antibody as well as cellular immune response were measured. The safety endpoints included weight changes and skin reactions. In study B, 32 rats were randomly assigned to four groups to receive low-dose, or medium-dose vaccine by NFI or NI, to observe pathological changes at the injection site following immunization.ResultsNo safety concern was noted associated with NFI of Ad5-nCoV. Comparable levels of neutralizing antibodies against various variants induced by NFI compared to NI at the same dosage.ConclusionThe NFI immunization would be considered as an alternative immunization method to replace the traditional NI for the Ad5-nCoV.